2010
DOI: 10.1101/cshperspect.a000646
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Speckles

Abstract: Nuclear speckles, also known as interchromatin granule clusters, are nuclear domains enriched in pre-mRNA splicing factors, located in the interchromatin regions of the nucleoplasm of mammalian cells. When observed by immunofluorescence microscopy, they usually appear as 20-50 irregularly shaped structures that vary in size. Speckles are dynamic structures, and their constituents can exchange continuously with the nucleoplasm and other nuclear locations, including active transcription sites. Studies on the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

40
750
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 752 publications
(793 citation statements)
references
References 74 publications
40
750
0
3
Order By: Relevance
“…Of particular interest is the non--uniform distribution of MBNL1 within the nucleus in some, but not all, cells where MBNL1 accumulates in structures resembling splicing factor 'speckles' (figure 2A arrowheads). While this is not unexpected, as MBNL1 has a well--documented role as an alternative splicing factor and splicing factors characteristically accumulate in speckles [25], it has not been documented previously. We therefore sought to confirm the identity of the structures accumulating MBNL1.…”
Section: ) Lens Epithlial Cells From Dm1 Patients Contain Cug Rna Fomentioning
confidence: 70%
See 1 more Smart Citation
“…Of particular interest is the non--uniform distribution of MBNL1 within the nucleus in some, but not all, cells where MBNL1 accumulates in structures resembling splicing factor 'speckles' (figure 2A arrowheads). While this is not unexpected, as MBNL1 has a well--documented role as an alternative splicing factor and splicing factors characteristically accumulate in speckles [25], it has not been documented previously. We therefore sought to confirm the identity of the structures accumulating MBNL1.…”
Section: ) Lens Epithlial Cells From Dm1 Patients Contain Cug Rna Fomentioning
confidence: 70%
“…A smaller proportion of cells show clear co--localization of MBNL1 with nuclear speckles containing splicing factors. Accumulation in splicing speckles is characteristic of many splicing factors, with the speckles thought to serve as a reservoir from which they are recruited to participate in splicing at sites of transcription when required [25]. The diffuse localization of MBNL1, while uncharacteristic for a pre mRNA splicing factor, is similar to the distribution seen for snRNP proteins associated with the minor U11/12 spliceosome, present at 1/100 th the amount of the major spliceosome [36--39] .…”
Section: Discussionmentioning
confidence: 99%
“…Subnuclear domains, so called nuclear speckles, correspond to sites with active transcription in the interchromatin regions. They are connected with the presence of splicing factors, but less with the accumulation of other factors participating on RNA processing in microscope localization studies (Spector & Lamond, 2011; Reddy et al ., 2012). Analogously to their animal orthologues (Liu et al ., 2014; Ping et al ., 2014), plant writers also show a similar punctate pattern (Zhong et al ., 2008) and co‐localize with the splicing factor SR34‐RFP.…”
Section: Discussionmentioning
confidence: 99%
“…This splicing factor, as well as the co‐localizing writers, shows a more diffuse pattern in the meristematic cells, whereas in the cells above the elongation zone the speckle pattern is more prevalent. This likely coincides with differential transcriptional activities in rapidly dividing and differentiated cells, similar to observations from animal systems (Tillemans et al ., 2006; Spector & Lamond, 2011; Reddy et al ., 2012). Because m 6 A affects splicing in mammals and D. melanogaster (Liu et al ., 2014; Ping et al ., 2014; Alarcón et al ., 2015a; Haussmann et al ., 2016; Lence et al ., 2016) possibly by recruiting splicing factors (Xiao et al ., 2016), it is interesting to speculate whether m 6 A could also regulate splicing in plants.…”
Section: Discussionmentioning
confidence: 99%
“…They contain transcription factors, 3 0 -end RNA processing factors, translation regulation factors and the large subunit of RNA polymerase II. 28,29 Jia et al have shown also that the inhibition of transcription changes the nucleoplasmic distribution of FTO, which becomes more concentrated at speckles. Of note, we observed different pattern of nucleoplasmic FTO staining in cells with different proliferation rates.…”
Section: Discussionmentioning
confidence: 99%